1982
DOI: 10.1080/00913847.1982.11947245
|View full text |Cite
|
Sign up to set email alerts
|

Mountaineering and Rock-Climbing Accidents

Abstract: In brief There were 71,655 rock climbers and mountaineers in the Grand Teton National Park from 1970 to 1980, and there were 144 accidents and 30 deaths. Because all climbers are required to register with park officials before climbing, accurate incidence rates can be determined. There were two accidents per 1,000 climbers per year, and this rate remained stable over the ten-year study period although the number of climbers increased. Characteristics associated with accidents included being the lead climber, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…Previous research has primarily focused on injuries sustained in traditional mountaineering and alpine climbing in adult participants. [1][2][3][4][5] More recent studies involving youth have predominantly examined finger injury and radiographic changes in small groups of elite climbers, located primarily in Germany, or focus on growth and development or anthropometrics. 7 8 10 33 39 40 Though the sample size originally calculated was not met, a high proportion (84%) of the competitive climbers approached were recruited for this study.…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has primarily focused on injuries sustained in traditional mountaineering and alpine climbing in adult participants. [1][2][3][4][5] More recent studies involving youth have predominantly examined finger injury and radiographic changes in small groups of elite climbers, located primarily in Germany, or focus on growth and development or anthropometrics. 7 8 10 33 39 40 Though the sample size originally calculated was not met, a high proportion (84%) of the competitive climbers approached were recruited for this study.…”
Section: Strengthsmentioning
confidence: 99%
“…Previous research has focused on injuries sustained in traditional rock climbing, ice climbing, mountaineering, and alpine settings in adult participants. [1][2][3][4][5] Injuries sustained in these activities consist largely of trauma resulting from falls and overhead rock fall, injuries from weather (such as frostbite), and negative altitude effects. 6 There has been a paucity of research examining injuries and risk factors in young climbers specifically.…”
mentioning
confidence: 99%
“…Studies of associations between climbing experience and injury risk have shown differing results. Bowie et al (1988) and Monasterio (2005) found, in contrast to some high‐altitude mountaineering epidemiological studies (McLennan & Ungersma, 1982; Schussman & Lutz, 1982), that climbers with a relatively long climbing experience were more frequently injured. Recent studies in sports and traditional climbing have reported the same tendencies (Paige et al, 1998; Gerdes et al, 2006).…”
mentioning
confidence: 92%
“…However, Schöffl and Kuepper (2006) report 3.1 injuries per 1000 climbing hours among the 443 competitors at the 2005 World Championships. Traumatic climbing injuries, excluding pulley ruptures, are dominated by lower extremity lesions, and have commonly resulted from falls while leading an outdoors climb on natural rock (McLennan & Ungersma, 1982; Schussman & Lutz, 1982; Bowie et al, 1988; Addiss & Baker, 1989; Malcolm, 2001; Monasterio, 2005). Studies of associations between climbing experience and injury risk have shown differing results.…”
mentioning
confidence: 99%
“…In contrast to traditional climbing, where most of the bodyweight is supported by the lower extremities, in sport climbing the upper extremities have to do most of the work which requires an excellent general upper body strength and a specific training program and strength of the muscles of the forearms and the hands [11,15,18,34,35]. To have a stable, supinated position in the climbing shoe and to increase the proprioceptive sensitivity of the toes and foot in order to use smallest footholds, climbing shoes are very thin and routinely worn several sizes smaller than street shoes [23,47].…”
Section: Sport Climbingmentioning
confidence: 99%